Using a Data-Driven Learning Approach to Teach English for Academic Purposes and Improve Higher Education Internationalisation - Pinto, Paula Tavares [UNESP] (Taylor & Francis, 2024)
The United Nations’ 2030 Agenda, established in 2015, aims to create a more sustainable future for the entire planet through 17 interconnected Sustainable Development Goals (SDGs). These SDGs were proposed to tackle global challenges such as poverty, inequality, climate change, peace, and justice. They mobilize all sectors of society in global, local, and individual actions involving academia and stakeholders. Despite widespread publicity, many remain unaware of these goals and their implementation in their own countries. To bridge this gap, we aim to explore how data-driven learning (DDL) can effectively be taught in thematic classes that enable educators to design engaging “hands-on” and “hands-off” activities to secondary and higher education students. This chapter aims to inspire ESL teachers and researchers to embrace an active, autonomous, corpus-based approach in the classroom.